Physical Activity as a Trigger for Anaphylaxis: Understanding Food-Dependent Exercise-Induced Anaphylaxis - Kamila Szewczyk; Bartłomiej Szewczyk; Weronika Hołownia; Paulina Pytel; Wiktoria Julia Krzesłowska; Szymon Wiśniewski (Kazimierz Wielki University, 2024)
Introduction: Food-dependent exercise-induced anaphylaxis (FDEIA) is a distinctive form of anaphylaxis, a severe and potentially life-threatening allergic reaction, that is triggered by physical activity following the consumption of specific food allergens. Unique in its manifestation, FDEIA embodies a complex interaction between food intake and exercise, making it a condition of noteworthy concern particularly among athletes and active individuals.   Aim of the study: This article endeavors to explore the multifaceted nature of food-dependent exercise-induced anaphylaxis, beginning with a foundational understanding of anaphylaxis and the specific dynamics involved in exercise-induced reactions.   Material and methods: Literature available in the PubMed database was reviewed using the following keywords: food-dependent exercise induced anaphylaxis; exercise induced-anaphylaxis; food allergies; pathogenesis of FDEIA; diagnosis of FDEIA; sport and anaphylaxis.   Conclusions: FDEIA is a unique and complex condition that requires a comprehensive understanding for effective management. By exploring its various aspects, from pathophysiology to diagnosis and treatment, we can better equip individuals with the knowledge and tools to navigate this condition and minimize the risk of potentially life-threatening reactions.